Urban playground. (2nd October 2021) - Gill, Tim
Abstract : The pandemic has led to an enforced diet of hyperlocal living. And many of us found some of its ingredients, including more time to ourselves, stronger connections with neighbours and the pleasures of nearby nature, all very much to our tastes.